Disability pension motivated income adjustment - Dag S. Holen (University of Oslo, Department of Economics, 2008)
One element of the Norwegian disability pension system makes the extent to which pension responds to changes in income in the last three years before disablement vary over different income profiles. This special feature is explored in order to identify an individual specific pension incentive for income adjustment. If disability is foreseen, this feature implies that there is a motive for increasing income in the years before disablement and through this increase pensions. Analysis on register data for all persons receiving disability pension 1992-2001 shows that the possibility to affect pensions increases income, indicating that disability to some extent is foreseen and that individuals strategically adjust their income in order to increase their pensions.
Keywords: 330; Erwerbsunfähigkeitsrente; Einkommen; Anpassung; Norwegen